Pulmonary and systemic hemodynamics are associated with myocardial injury in the acute respiratory distress syndrome. (1st July 2020) - Metkus, Thomas S; Mathai, Stephen C; Leucker, Thorsten; Hassoun, Paul M; Tedford, Ryan J; Korley, Frederick K
Abstract : Background: Whether right and left heart hemodynamics are associated with myocardial injury in the acute respiratory distress syndrome (ARDS) is not known. Methods: We performed a retrospective cohort study of subjects who had right heart catheterization within the ALVEOLI trial and Fluid and Catheter Treatment Trial. Myocardial injury was assessed using a highly sensitive troponin assay (hsTn; Abbot ARCHITECT). Hemodynamic variables included right atrial pressure, pulmonary artery wedge pressure, cardiac index and stroke volume, pulmonary vascular resistance, pulmonary arterial compliance, and pulmonary effective arterial elastance. We performed linear, logistic, and Cox regression to determine the association of hemodynamic variables with myocardial injury and to determine if hemodynamics mediated the association between myocardial injury and death. Results: Among 252 ARDS patients, median day 0 troponin was 65.4 (13.8–397.8) ng/L. Lower cardiac index (β −0.23 SE 0.10; P < 0.001) and stroke volume (β −0.26 SE 0.005; P < 0.001), higher pulmonary vascular resistance (β 0.22 SE 0.11; P < 0.001), lower pulmonary arterial compliance (β −0.24 SE 0.06; P < 0.001), and higher arterial elastance (β 0.27 SE 0.43; P < 0.001) were associated with greater myocardial injury in univariable and adjusted models. Changes in stroke volume, cardiac index, pulmonary arterial compliance, pulmonary vascular resistance, and arterial elastance were all associated with progressive myocardial injury over three days. hsTn levels were associated with mortality; however, the association was attenuated after adjustment for each of stroke volume, pulmonary vascular resistance, pulmonary arterial compliance, and arterial elastance. Conclusion: Pulmonary vascular hemodynamics are associated with myocardial injury in ARDS, while filling pressures are not. Pulmonary vascular disease may represent a treatable contributor to myocardial injury in ARDS.